Non-linear mini-max problem of multi-stop flight routes - Srećko Krile; Marina Krile; Petr Průša (Transport, 2015)
The major change in trends of air transport development is to increase operating efficiency, productivity and profitability. Airline companies (air operators or carriers) can ensure significant fuel savings and better utilization of airplanes capacity. So they need better transport planning tool for costs minimization on a voyage route with multiple loading/unloading airports (multi-stop routes).The existing routes can be re-optimized (improved) or alternative routes can be offered instead. In this research the efficient heuristic algorithm for optimal transportation of N different loads (e.g. passenger contingent) for the airplane with limited capacity is being developed. The main goal of algorithm is to reduce the idle capacity on the route, to decrease expenses and to increase revenue. Through many test examples we can see that such approach functions very good and calculation complexity is under control.